Cultural and symbolic dimensions of the migration-development nexus - Tomei, G (International Migration Institute, 2011)
Migration is not a natural phenomenon, completely independent of historical and political contexts on the one hand and individual and collective reactions to them on the other. And development does not appear suddenly, as the result of impersonal forces driving migrants to directly or indirectly support it. Migration can generate development only through intentional actions, with community wellbeing in migrants’ home countries acting as the anchor for individuals, associations and governments; and by providing a wider setting in which this ‘intention’ is played out, revealing the place for cultural, symbolic and moral dimensions of transnational community belonging and membership. Community acts as a cultural ‘compass’, determining migrants’ attitudes towards the development of their home country. Strong communitarian membership is generally associated with real engagement in the development issues of members left behind (as part of the collective self), but varies according to the structural features of the migrants’ networks, the way in which migrants define networks as their own communities, the results of past communitarian memories and future communitarian imaginations on actual communitarian experience and perceptions. I discuss these issues in the light of recent theoretical debates on structureagency dynamics.